Case Report: two cases of anti-neutrophil cytoplasmic antibody-associated vasculitis involving large vessels - Zhang, Hanyu; Yan, Dingfang; Wei, Yuehua; He, Yun; Chang, Junjie; Zhang, Wenjun (Frontiers in Cardiovascular Medicine, 2024)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of systemic diseases caused by a combination of many factors, including genetics, environment, and immunity. AAV is characterized by predominantly small-vessel involvement and has a variety of clinical manifestations. Small-vessel lesions of the kidneys and lungs are common, and lesions of medium-sized arteries may also present, but the involvement of large arteries and their primary branches is very rare. This report delineates two instances of AAV with large arterial involvement, one case presenting with lesions of the aortic valve and the other with lesions of the pulmonary artery. The first case involved a 57-year-old man with no underlying diseases. Transthoracic echocardiography showed thickening of the left and right coronary valves of the aortic valve with enhanced echogenicity, moderate echogenic masses were seen on both valve leaflets, and the leaflets had restricted opening and poor closure. Blood tests showed positive perinuclear anti-neutrophil cytoplasmic antibodies (p-ANCA) and anti-myeloperoxidase (MPO) antibodies. The patient's aortic valve thickening virtually disappeared after treatment with hormones combined with immunosuppressive agents. The second case involved a 60-year-old woman whose transthoracic echocardiography and CT (computed tomography) angiography of the pulmonary arteries showed wall thickening of the main pulmonary artery and the proximal left and right pulmonary arteries, leading to luminal stenosis. Blood tests showed positive cytoplasmic anti-neutrophil cytoplasmic antibodies (c-ANCA) and anti-proteinase 3 (PR 3) antibodies. The patient's pulmonary artery wall thickening reduced after receiving hormones in combination with immunosuppression but she died of heart failure during subsequent treatment. The patient had been diagnosed with tuberculosis six months earlier and had been poorly treated with anti-tuberculosis therapy. The involvement of large arteries in AAV is a rare and critical condition with rapid progression and a high mortality rate. Early recognition of this type of AAV and aggressive immunosuppressive therapy may facilitate the reversal of the vascular lesion and a reduction in the risk of patient death.